2021
DOI: 10.1371/journal.pone.0253920
|View full text |Cite
|
Sign up to set email alerts
|

Causes contributing to the excess maternal mortality risk for women 35 and over, United States, 2016–2017

Abstract: To better understand age-related disparities in US maternal mortality, we analyzed 2016–2017 vital statistics mortality data with cause-of-death literal text (actual words written on the death certificate) added. We created a subset of confirmed maternal deaths which had pregnancy mentions in the cause-of-death literals. Primary cause of death was identified and recoded using cause-of-death literals. Age-related disparities were examined both overall and by primary cause. Compared to women <35, the 2016–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“… 23 , 24 It was found that the risk of increased maternal mortality for women aged 35 and up was concentrated in a few causes of death, and much of this excess mortality can be avoided. 25 , 26 In connection with the results of this study, the promotional efforts can be carried out in addition to forming good behavior attitudes. Therefore it is also very important to pay attention to the knowledge factor of pregnant women by carrying out health promotion strategies by empowering health cadres, so that the intentions of the pregnant women can be strengthened by adding more knowledge regarding mother's pregnancy care.…”
Section: Discussionmentioning
confidence: 72%
“… 23 , 24 It was found that the risk of increased maternal mortality for women aged 35 and up was concentrated in a few causes of death, and much of this excess mortality can be avoided. 25 , 26 In connection with the results of this study, the promotional efforts can be carried out in addition to forming good behavior attitudes. Therefore it is also very important to pay attention to the knowledge factor of pregnant women by carrying out health promotion strategies by empowering health cadres, so that the intentions of the pregnant women can be strengthened by adding more knowledge regarding mother's pregnancy care.…”
Section: Discussionmentioning
confidence: 72%
“…11 Maeðradauði eykst með haekkandi aldri maeðra. 12 Laekkun maeðradauða er eitt af átta þúsaldarmarkmiðum Sameinuðu þjóðanna. 2,6,8 Talsverður árangur hefur náðst, en ekki fullnaegjandi í löndum sem eru verst sett.…”
Section: Maeðradauði á íSlandi 1976-2015unclassified
“…People are waiting longer into adulthood to conceive. Compared to pregnant people younger than age 35, the 2016–2017 US maternal mortality rate was twice as high for those aged 35–39, four times higher for those aged 40–44, and 11 times higher for those aged 45–54 years [13 ▪ ]. While age is not necessarily modifiable, targeting the chronic medical conditions that are contributing to increased risk of morbidity for older pregnant people is important to address.…”
Section: Modifiable Risk Factors For Morbidity In the Interpregnancy ...mentioning
confidence: 99%